Efeito do alcaloide Curina nas vias de transdução de sinais TLR4/NFκB em granulócitos do pulmão no modelo experimental de lesão pulmonar aguda - Ferreira, Larissa Adilis Maria Paiva (2020)
Acute lung injury (ALI) and its most severe form, acute respiratory distress syndrome (ARDS) are inflammatory diseases that affect the lungs, with rupture of the alveolar-capillary barrier and loss of lung compliance orchestrated by an intense mediated inflammatory process, mainly by neutrophils that culminate with the diffuse alveolar data and tissue hypoxia. So far, there is no adequate pharmacotherapy, so the search for pharmacological alternatives that improve the inflammatory condition, tissue damage and restore pulmonary architecture is promising. In this context, Curine, a naturally occurring bisbenzylisoquinoline alkaloid, with antiallergic, analgesic and anti-inflammatory properties is the target of this study, which aimed to demonstarte the mechanism (s) of action of the alkaloid in the experimental model of acute lung injury (ALI). For this purpose, male BALB / c mice were challeged with lipopolysaccharide (LPS) and treated with Curine one, 24 and 48 hours after the challenge and, 72 hours after LPS administration, the animals were euthanized and biological material was collected for analysis. Treatment with curine inhibited (p<0,05) cell migration to bronchoalveolar lavage fluid (BALF), which was mainly dependent on neutrophil inhibition. In addition, curine restored the pulmonary architecture, reducing edema, vascular permeability and reducing the concentration of total proteins in the BALF as well as the Wet / Dry (W/D) ratio of the lung. Curine also decreased (p<0,05) the production of inflammatory cytokines TNF-α, IL-1β, and IL-6. Surprisingly, the curine demonstrated its anti-inflammatory activity via negative modulation in the expression of the TLR-4 receptor, with a consequent decrease in phosphorylation and activation of the p65 portion of NFκB, thus interfering in the inflammatory process characteristic of ALI. In conclusion, the treatment with curine reversed the inflammatory and edematogenic conditions in LPA, via TLR4 / NFκB signaling, making it a promising molecule, candidate for a possible drug, to be tested in clinical trials in order to be included in the arsenal small and restricted number of drugs for acute respiratory distress syndrome.